Study of soil cover of Veronica spuria L. populations in Ile Alatau mountains, Kazakhstan - Yerkebulan Balkybek; Bekzat Tynybekov; Kanat Kulymbet; Ussen Kurmanbay; Zoya Umirbayeva; Zinat Nurakyn; Assiya Myltykbayeva; Alibek Ydyrys; Murat Toktar (EQA)
The article studies the natural conditions of soils of Kimasar, Big Almaty and Kaskelen gorges belonging to the Ile Alatau mountain range. From the received soil samples the types of soils, morphological features of soils, amounts of nutrient elements (mobile nitrogen, mobile phosphorus, mobile potassium), humus content, reaction of soil medium (pH), carbon content in soil layers (CO2), mobile forms of heavy metals (Zn, Cu, Cd, Pb), sum of salts in soils (salt composition) and mechanical composition of soils were determined. According to morphological features of soils, mountain-meadow dark chestnut soils (Population-1), mountain-meadow soddy chestnut soils (Population-2), and mountain-thermoxerophilic dark chestnut soils (Population-3). The amount of humus, which is the main indicator of soil fertility, in the dark chestnut soils was higher compared to the soils of the other two studied gorges, i.e. it was 3.44-8.54%. On mobile amounts of nutrient elements in dark chestnut soils revealed high amounts of mobile nitrogen, phosphorus and potassium, nitrogen – 547.6-100.8 mg/kg, phosphorus – 28-46 mg/kg, potassium – 170-450 mg/kg. Among microelements mobile forms of zinc (Zn), copper (Cu), lead (Pb) did not exceed MPC of these elements in all types of soils, only mobile cadmium (Cd) exceeded MPC several times. By mechanical composition of soil dark chestnut soils has light loamy (24,69 %), chestnut soils has light loamy (28,52 %), dark chestnut soils was sandy (7,32 %). In terms of salt content, all soil samples turned out to be non-saline (salt content below 0.025%).